Development of Smart Adventure Games to Improve the Readiness of the Initial Ability of Reading, and Writing (CALIS) on Early Childhood - Linda Dwiyanti; Rosa Imani Khan; Epritha Kurniawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
Based on these circumstances, this study aims to develop an appropriate game to improve readiness of the initial ability of reading, and writing on early childhood called